THE INFLUENCE OF WIRE PITCH TO THE WIRE AND TUBE HEAT EXCHANGER EFFICIENCY IN FREE CONVECTION - I Made Arsana (Jurnal Penelitian Saintek, 2016)
Wire and Tube heat exchanger consists of coiled tube and wire sticked on the two sides of it in normal direction of the tube. The ability of this heat exchanger to dissipate heat is shown by the overall surface efﬁ ciency from array of ﬁ ns or called as heat exchanger efﬁ ciency. The wire which functions as a ﬁ n is the expansion of the outer surface of tube, so that it expands the surface of free convection heat transfer and transfers heat from the heat exchanger to the outside surroundings. The ﬁ n efﬁ ciency commonly depends on its material, geometry and environment where it is used. In this research, the inﬂ uence of the wire pitch to the heat exchanger was examinated. Tthree designs of the heat exchanger with different wire pitch namely (pw/Lw = 0.015; pw/Lw = 0.029 dan pw/Lw = 0.044) were tested into ﬁ ve levels of entrance ﬂ uids temperature (40, 50, 60, 70, and 80 0 C). The ﬁ nding of this study was that the heat exchanger pw/Lw = 0.029 evenly produced the highest efﬁ ciency.